A kind of alum-free wide powder and preparation method thereof

By using a multi-component composite system and a synergistic modifier to build a crosslinking network, the problem of insufficient toughness and muscle feel during the cooking process of alum-free wide powder is solved, and the cooking resistance, muscle and high transparency effects of wide powder are achieved.

CN119745041APending Publication Date: 2025-04-04DINGXI ZEYUAN FOOD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510172228.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing alum-free wide powder is not tough and chewy during the cooking process, and is prone to softening or breaking, making it difficult to meet the needs of actual consumption scenarios.

Method used

A multi-component composite system of sweet potato starch, tapioca starch and corn starch is adopted, and a high-stability cross-linking network is constructed by adding konjac gum, xanthan gum, chitosan, agarose and polyols, and a high-stability cross-linking network is constructed, combining physical cross-linking and chemical cross-linking technology.

Benefits of technology

It significantly improves the mechanical strength and processing performance of wide powder, gives wide powder a boil-resistant, chewy and elastic texture characteristics, and solves the problems of insufficient transparency and rough surface of traditional alum-free wide powder.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119745041A_ABST
    Figure CN119745041A_ABST
Patent Text Reader

Abstract

The present application relates to the field of food processing, discloses a kind of alum-free wide flour and preparation method thereof, including: it is composed of the following components in percentage by weight: sweet potato starch 55%-65%; tapioca starch 10%-20%; corn starch 5%-10%; konjac gum 2%-5%; xanthan gum 0.5%-2%; chitosan 0.1%-0.3%; agarose 0.5%-1.5%; polyol 0.5%-2%, the polyol is glycerol or sorbitol; weak acid stabilizer 0.3%-0.5%, the weak acid stabilizer is sodium citrate or sodium lactate; water 20%-30%; the moisture content of the sweet potato starch is 10%-14%, the viscosity is 5000-7000mPa·s refined sweet potato starch, and the tapioca starch is an industrial-grade tapioca starch with a gelatinization temperature of 62-70. By adopting a multi-component composite system of sweet potato starch, tapioca starch and corn starch, and optimizing its proportion ratio, a basic network structure with high stability is constructed. By combining physical cross-linking and chemical cross-linking technology, the wide noodles can still maintain excellent chewiness and cooking resistance without alum.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of food processing, in particular to alum-free broad flour and a preparation method thereof. Background Art

[0002] As consumers' demands for food health and safety increase, alum-free wide noodles have gradually attracted market attention as a new type of healthy food. The production of traditional wide noodles usually relies on alum as a texture modifier. The addition of alum can give the wide noodles excellent chewiness, cooking resistance and processing performance, and the product has high transparency. However, the aluminum element in alum is potentially harmful to human health, and long-term consumption may cause health problems such as neurological diseases. Therefore, finding natural modifiers that can replace alum and developing related technologies for alum-free wide noodles have become important research directions in the food industry.

[0003] In the existing technology, the research and development of alum-free wide noodles mainly focuses on the modification of starch matrix and the optimization of cross-linking technology. For example, some technologies modify a single starch system such as sweet potato starch or corn starch in combination with a single natural gum, attempting to improve the texture properties of wide noodles by adjusting gelatinization conditions and process parameters. However, such methods often find it difficult to take into account the chewiness, transparency and cooking resistance of wide noodles. In addition, there are also technologies that attempt to improve the performance of wide noodles through chemical cross-linking agents, but the safety and green properties of chemical cross-linking agents are difficult to meet the high standards of the current food industry.

[0004] The existing technology still has significant problems in the research and development of alum-free wide noodles. That is, due to the lack of systematic multi-component composite system design and synergistic modification strategy, the toughness and chewiness of alum-free wide noodles are insufficient, and they are easy to become soft or broken during the cooking process, which is difficult to meet the needs of actual consumption scenarios. In traditional wide noodles, due to the lack of alum support, the wide noodles may be over-gelatinized and structurally damaged during the cooking process, showing softness, gelatinization, and even dispersion. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides an alum-free wide noodle and a preparation method thereof, which solves the problems that the prior products lack toughness and chewiness and are easily softened or broken during the cooking process.

[0006] To achieve the above objectives, the present invention is implemented through the following technical scheme: a non-alum wide flour, comprising: it is composed of the following components in weight percentage: 55%-65% sweet potato starch;

[0007] Cassava starch 10%-20%;

[0008] Corn starch 5%-10%;

[0009] Konjac gum 2%-5%;

[0010] Xanthan gum 0.5%-2%;

[0011] Chitosan 0.1%-0.3%;

[0012] Agarose 0.5%-1.5%;

[0013] 0.5%-2% polyol, wherein the polyol is glycerol or sorbitol;

[0014] Weak acid stabilizer 0.3%-0.5%, wherein the weak acid stabilizer is sodium citrate or sodium lactate;

[0015] Moisture 20%-30%.

[0016] Preferably, the sweet potato starch is a refined sweet potato starch having a moisture content of 10%-14% and a viscosity of 5000-7000 mPa·s, and the cassava starch is an industrial grade cassava starch having a gelatinization temperature of 62-70°C.

[0017] Preferably, the amylose content of the corn starch is 25%-28%, and the particle size distribution range is 5-20 microns.

[0018] Preferably, the viscosity of the konjac gum is 20000-30000 mPa·s in a 0.5% aqueous solution under the condition of 25, and the particle size is 80-120 meshes.

[0019] Preferably, the xanthan gum is food grade xanthan gum with a purity of 95% or more, and its solubility is preferably above 85 and completely dissolved.

[0020] Preferably, the molecular weight of the chitosan is 100,000-200,000 Daltons, the degree of deacetylation is 70%-90%, and its dispersibility is preferably such that a uniform and stable solution is formed under pH 4-6.

[0021] Preferably, the molecular weight of the agarose is 150,000-200,000 Daltons, its dissolution temperature is 85-90°C, and its gelation temperature is 30-40°C.

[0022] Preferably, the polyol is glycerol, and its content is 1%-2%, which is used to construct a cross-linked network that forms hydrogen bonds with starch molecular chains.

[0023] Preferably, the weakly acidic stabilizer is sodium citrate, and its addition amount is controlled at 0.3%-0.4%, and its function is to maintain the pH value of the slurry at 5.5-6.5 to stabilize the molecular cross-linking.

[0024] The present invention also provides a method for preparing alum-free wide powder, comprising the following steps:

[0025] Step 1, mixing sweet potato starch, tapioca starch and corn starch, adding konjac gum, xanthan gum, chitosan, agarose, polyol and weak acid stabilizer to form a dry mixture;

[0026] Step 2: Add the dry mixture into water and stir evenly to form a slurry;

[0027] Step 3: Heat the slurry to 65-90°C, maintain for 8-15 minutes, and perform dynamic shearing to form a preliminary cross-linked network;

[0028] Step 4: Extruding the gelatinized slurry into a wide powder shape through a die;

[0029] Step 5: Immerse the formed wide noodles in cooling water at a temperature of 5-10°C.

[0030] Step 6: Place the cooled wide flour in a drying device and dry at 45-55 degrees to a moisture content of 12%-14%.

[0031] The present invention provides a non-aluminum wide powder and a preparation method thereof. It has the following beneficial effects:

[0032] 1. The present invention adopts a multi-component composite system of sweet potato starch, cassava starch and corn starch, and optimizes their proportions to construct a high-stability basic network structure. Combining physical cross-linking and chemical cross-linking technology, the wide noodles still maintain excellent chewiness and cooking resistance under alum-free conditions. Compared with the problems of insufficient toughness and easy breakage that are prone to occur in the single starch system in the prior art, the mechanical strength and processing performance of the wide noodles are significantly improved.

[0033] 2. The present invention forms a high-density cross-linked network during starch gelatinization by adding synergistic modifiers such as konjac gum, xanthan gum and chitosan, and at the same time enhances the dynamic elasticity and high temperature resistance of wide noodles. In the prior art, wide noodles have a loose texture after alum is removed and are easily softened during cooking. The present invention successfully overcomes this problem and gives wide noodles the texture characteristics of being resistant to cooking, chewy and elastic.

[0034] 3. The present invention adopts food-grade components as texture modifiers, including natural polymers such as konjac gum, chitosan, and agarose to replace alum, avoiding the potential harm of aluminum additives to human health. Compared with the method of relying on chemical additives in the prior art, the present invention not only improves the safety of the product, but also reduces the chemical pollution of production to the environment, conforms to the development trend of green food and healthy consumption, and solves the defect that traditional processes are not environmentally friendly.

[0035] 4. The present invention uses refined component design and parameter control. The present invention utilizes the amylose characteristics of sweet potato starch and combines the physical gelation effect of agarose to form a highly uniform molecular network structure of wide flour after cooling. Finally, a wide flour product with high transparency and smooth taste is obtained. Compared with traditional alum-free wide flour, the present invention solves the sensory defects of insufficient transparency and rough surface of wide flour products, and the product is more in line with market demand. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The present invention is a flow chart of the method. DETAILED DESCRIPTION

[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0038] Example:

[0039] Please see attached Figure 1 , the embodiment of the present invention provides a kind of alum-free wide flour, comprising: it is composed of the following components in weight percentage: 55%-65% of sweet potato starch;

[0040] Cassava starch 10%-20%;

[0041] Corn starch 5%-10%;

[0042] Konjac gum 2%-5%;

[0043] Xanthan gum 0.5%-2%;

[0044] Chitosan 0.1%-0.3%;

[0045] Agarose 0.5%-1.5%;

[0046] Polyol 0.5%-2%, polyol is glycerol or sorbitol;

[0047] Weak acid stabilizer 0.3%-0.5%, the weak acid stabilizer is sodium citrate or sodium lactate;

[0048] Moisture 20%-30%.

[0049] Sweet potato starch (60%)

[0050] Sweet potato starch, as the main matrix of wide noodles, provides good viscoelasticity and structural support. Refined sweet potato starch with a moisture content of ≤14% and a viscosity of 5000-7000mPa·s is preferred. Low moisture content avoids excessive agglomeration during processing, ensuring the smooth processing of wide noodles and subsequent texture properties. High viscosity properties further ensure the tensile strength and shape stability of wide noodles after gelatinization, especially during dynamic shearing.

[0051] Tapioca starch (15%)

[0052] The main function of cassava starch is to improve the smooth taste and elasticity of wide noodles. The industrial grade cassava starch with a gelatinization temperature of 62-70℃ is preferred. The low gelatinization temperature ensures that it can gelatinize synchronously with sweet potato starch and reduce the uneven gelatinization phenomenon. The unique low amylose content of cassava starch makes the surface of wide noodles smooth and non-sticky, which improves sensory acceptance.

[0053] Corn starch (8%)

[0054] Corn starch has an amylose content of 25%-28% and a particle size of 5-20 microns. During the gelatinization process, amylose easily forms a rearranged molecular chain structure with sweet potato starch, which improves the boiling resistance and fracture toughness of wide noodles. The distribution of its particle size allows a uniform filling structure to be formed between starch particles, further optimizing the processing stability of wide noodles.

[0055] Konjac gum (3.5%)

[0056] Konjac gum is the main cross-linking enhancer, and its 0.5% aqueous solution has a viscosity of 20,000-30,000 mPa·s at 25°C. The high molecular chain structure of konjac gum can form a preliminary physical cross-link with sweet potato starch, giving the wide noodles a chewy feel and toughness. Konjac gum with a particle size of 80-120 mesh is easier to disperse evenly, avoiding agglomeration of the slurry during the gelatinization stage.

[0057] Xanthan gum (1.5%)

[0058] Xanthan gum acts as an auxiliary cross-linking component and synergistically with konjac gum. High-purity (≥95%) xanthan gum can dissolve quickly during the gelatinization stage, combining with starch granules and konjac gum to form a dynamic three-dimensional network, improving the dynamic stability and shear resistance of the system. This network structure provides continuous support for the processing of wide noodles and avoids deformation.

[0059] Chitosan (0.2%)

[0060] The cationic properties of chitosan make it possible for electrostatic adsorption between molecules. Its molecular weight is 100,000-200,000 Daltons and its degree of deacetylation is 70%-90%. In the pH range of 4-6, chitosan can strengthen the intermolecular bonding force with starch and other components through electrostatic adsorption, thereby improving the fracture toughness and boiling resistance of wide noodles.

[0061] Agarose (1.0%)

[0062] Agarose gels during the cooling stage, with a molecular weight of 150,000-200,000 Daltons, a dissolution temperature of 85-90°C, and a gelation temperature of 30-40°C. After cooling, the physical gel network constructed by agarose optimizes the molecular arrangement, making the molecular distribution inside the wide powder more uniform, reducing light scattering, and significantly improving transparency.

[0063] Polyol (1.5%, glycerol)

[0064] Glycerol forms hydrogen bonds with starch molecular chains through its hydroxyl groups, further strengthening the bonding force between molecular chains. The cross-linking enhancement optimizes the mechanical properties of wide flour, significantly improving its boiling resistance and shape retention. The addition of glycerol can also improve the fluidity of the slurry and make the gelatinization process more stable.

[0065] Weak acid stabilizer (0.4%, sodium citrate)

[0066] Sodium citrate adjusts the pH of the slurry to 5.5-6.5, creating an acid-base environment suitable for electrostatic adsorption of chitosan. At the same time, it stabilizes the intermolecular cross-linking during the gelatinization process to prevent system instability caused by pH fluctuations.

[0067] The sweet potato starch is refined sweet potato starch with a moisture content of 10%-14% and a viscosity of 5000-7000mPa·s, and the cassava starch is industrial-grade cassava starch with a gelatinization temperature of 62-70.

[0068] The amylose content of corn starch is 25%-28%, and its particle size distribution ranges from 5 to 20 microns.

[0069] The viscosity of konjac gum is 20000-30000 mPa·s in 0.5% aqueous solution under 25 conditions, and its particle size is 80-120 mesh.

[0070] The xanthan gum is food grade xanthan gum with a purity of more than 95%, and its solubility is preferably more than 85 and completely dissolved.

[0071] The molecular weight of chitosan is 100,000-200,000 Daltons, the degree of deacetylation is 70%-90%, and its dispersion is preferably such that a uniform and stable solution is formed under pH 4-6.

[0072] The molecular weight of agarose is 150,000-200,000 Daltons, its dissolution temperature is 85-90°C, and its gelation temperature is 30-40°C.

[0073] The polyol is glycerol, with a content of 1%-2%, which is used to construct a cross-linked network that forms hydrogen bonds with starch molecular chains.

[0074] The weak acid stabilizer is sodium citrate, and its addition amount is controlled at 0.3%-0.4%. Its function is to maintain the pH value of the slurry at 5.5-6.5 to stabilize the molecular cross-linking.

[0075] The present invention also provides a method for preparing alum-free wide powder, comprising the following steps:

[0076] Step 1, mixing sweet potato starch, tapioca starch and corn starch, adding konjac gum, xanthan gum, chitosan, agarose, polyol and weak acid stabilizer to form a dry mixture;

[0077] Step 2: Add the dry mixture into water and stir evenly to form a slurry;

[0078] Step 3: Heat the slurry to 65-90°C, maintain for 8-15 minutes, and perform dynamic shearing to form a preliminary cross-linked network;

[0079] Step 4: Extruding the gelatinized slurry into a wide powder shape through a die;

[0080] Step 5: Immerse the formed wide noodles in cooling water at a temperature of 5-10°C.

[0081] Step 6: Place the cooled wide flour in a drying device and dry at 45-55 degrees to a moisture content of 12%-14%.

[0082] In this embodiment, sweet potato starch, cassava starch and corn starch are weighed and mixed in weight percentages of 60%, 15% and 8%, respectively. Sweet potato starch is used as the main component, and its preferred moisture content does not exceed 14%, and the viscosity is controlled at 5000-7000mPa·s. Cassava starch has a low gelatinization temperature (62-70), and its addition amount is about 25% of the mass of sweet potato starch. It can form a synergistic effect with sweet potato starch to improve the structural stability and elasticity of wide flour. The straight chain starch content of corn starch is controlled at 25%-28%, and its particle size distribution is 5-20 microns, which can fill the gaps in the starch network and provide molecular chain rearrangement ability during gelatinization.

[0083] Generally, konjac glucomannan is the key component for building a preliminary cross-linked network, and its addition is 3.5% of total mixture. As a selection, the viscosity of konjac glucomannan in the present embodiment is 20000-30000mPas (0.5% aqueous solution, under 25 conditions), and particle diameter is 80-120 order, can be evenly dispersed in starch matrix, and fully combines with subsequent hydration process. Xanthan gum addition is 1.5%, and its purity is not less than 95%, can form the viscoelastic network of enhancement in coordination with konjac glucomannan.

[0084] Specifically, chitosan (0.2%) is added in this embodiment to enhance the electrostatic adsorption effect, and its molecular weight range is 100,000-200,000 Daltons, and the degree of deacetylation is 70%-90%. In a possible implementation, the dispersion of chitosan requires the use of a weak acid stabilizer (sodium citrate) to adjust the pH value of the system to the range of 5.5-6.5, so as to achieve the best ion adsorption effect.

[0085] In addition, in order to further improve the stability of the cross-linked network, polyol (glycerol) is added in this embodiment, and its addition amount is 1.5%. Glycerol molecules form hydrogen bonds with starch molecular chains through their hydroxyl groups, which initially improves the bonding ability of the molecular chains. The addition of glycerol can also improve the lubricity of the mixture and make the subsequent hydration more uniform.

[0086] In the above-mentioned component mixing process, in some embodiments, a low-speed stirring device (50rpm) can be adopted to stir, and the duration is 5 minutes. Low-speed stirring can avoid producing too much static accumulation in the mixing process, and ensures that each component is evenly distributed. In a kind of optimization implementation, in order to further improve the mixing effect, a twin-screw mixer can be selected, which can reduce agglomeration in the mixing process, and ensures that the larger component of particle size such as konjac glucomannan is evenly dispersed.

[0087] The uniformity of the mixture can be verified by sieving experiments. For example, when the mixture is sieved with an 80-mesh screen, the mass of the sieved material should not be less than 95% of the total mass of the mixture. Specifically, the particle size distribution of the mixed material should be controlled within the range of 0.1-1mm to ensure that there is no obvious unevenness in the subsequent hydration reaction.

[0088] In this embodiment, the dry mixture obtained in step 1 is added to water at a mass ratio of 1:2.5. The purity of the water is required to be laboratory grade deionized water to avoid the interference of intermolecular forces caused by impurities in the water. The total mass of the dry mixture and the mass of the added water satisfy the following relationship:

[0089] This ratio can ensure complete hydration of the components without causing the viscosity of the slurry to be too low due to excessive water.

[0090] Generally, stirring needs to be done in a high-speed mixer, with a stirring speed of preferably 1000 rpm and a stirring time of 8 minutes. As an option, stirring can be performed at a low speed of 500 rpm for 2 minutes at the beginning of stirring to prevent agglomeration of the powder when it is added to the water, and then gradually increased to the target speed. This staged stirring method can effectively reduce the possibility of powder agglomeration during the mixing process.

[0091] Specifically, the stirring device can be a double-screw propeller stirrer, which has a strong dispersing ability and is suitable for the preparation of high-viscosity slurry. In a possible implementation, a stirring device with a heating function can be used to control the stirring temperature within the range of 25-30 to further improve the dissolution efficiency of the components.

[0092] In this embodiment, in order to ensure the uniformity of the slurry, after the stirring is completed, the slurry needs to be filtered through an 80-mesh screen to remove any remaining particles or agglomerates. This operation can ensure the final dispersibility of the slurry and reduce the thermal unevenness caused by the presence of particles in the subsequent gelatinization stage.

[0093] During the slurry formation process, sodium citrate begins to play a buffering role and adjusts the pH value of the slurry to between 5.5 and 6.5. This acid-base environment can provide the best electrostatic adsorption conditions for chitosan and reduce the pH drift of the slurry during the static process. Polyols (glycerol) begin to form preliminary hydrogen bond cross-linking with starch molecular chains through their hydroxyl groups. Although the cross-linking at this stage is not complete, it provides a basis for the molecular chain bonding in the subsequent gelatinization stage.

[0094] In some embodiments, in order to ensure the stability of the slurry, the slurry may be left to stand for 10 minutes after stirring to allow the interaction between the components to fully occur. During the standing process, the adsorption reaction between the chitosan molecules and the starch particles is gradually accelerated to form a more uniform preliminary network structure.

[0095] In an optimized implementation, the dynamic viscosity of the slurry can be measured by a rotational viscometer. For the slurry prepared in this embodiment, its dynamic viscosity value is generally controlled between 5000-8000 mPa·s (measurement conditions: 25, shear rate 100s -1 If the viscosity is lower than this range, it may indicate too much water or poor mixing; if the viscosity is too high, it may mean that the components are not fully dispersed.

[0096] In this embodiment, the slurry obtained in step 2 is gradually heated to 65°C, and then continued to be heated to 90°C under stirring conditions, and the heat preservation time is 12 minutes. Dynamic shearing is adopted in the gelatinization process, and the shear rate is controlled at 50 rpm. This condition can effectively promote the uniform expansion and dispersion of starch particles, while ensuring that the slurry system does not stratify or stick during the heating process.

[0097] In general, the choice of gelatinization temperature directly affects the swelling behavior of starch particles. The gelatinization starting temperature of sweet potato starch is about 65, while the gelatinization range of cassava starch is 62-70. As an option, this embodiment gradually increases the temperature to synchronize the gelatinization process of the two starches, thereby avoiding the structural inhomogeneity caused by local gelatinization differences.

[0098] Specifically, during the gelatinization process, the sweet potato starch granules swell, and physical cross-links are gradually established between the amylose and the xanthan gum and konjac gum molecular chains. This cross-linking is described by the following formula:

[0099] in:

[0100] It represents the hydrogen bonding energy, which is provided by the hydroxyl groups of the polyol and the starch molecular chains;

[0101] The van der Waals force is the main mechanism of synergistic cross-linking between konjac gum and xanthan gum.

[0102] During the gelatinization process, the cationic properties of chitosan also begin to emerge, and stable crosslinking points are formed between its molecules and the surface of starch particles through electrostatic adsorption. This effect is significantly affected by the pH of the slurry. In this embodiment, sodium citrate has adjusted the pH value to between 5.5 and 6.5, providing an optimal environment for the adsorption of chitosan.

[0103] In some embodiments, in order to ensure the stability of the gelatinization reaction, a dynamic temperature control system can be set in the gelatinization equipment to control the heating rate of the slurry at 3 / minute. This rate can avoid uneven heat distribution caused by rapid heating, especially when the slurry volume is large.

[0104] As a possible implementation, the present embodiment adopts a double-screw stirring device to achieve uniform dynamic shearing. The main effect of dynamic shearing is to maintain the fluidity of the slurry during heating to prevent the macromolecular components from forming agglomeration locally. In addition, shearing can also destroy the weak aggregation force between starch particles, making it easier for konjac gum and xanthan gum molecules to enter the molecular chain gap.

[0105] After gelatinization, the dynamic viscosity of the slurry is generally controlled between 20000-30000 mPa·s (measurement conditions: 90, shear rate 50s -1 If the viscosity is lower than this range, it may indicate insufficient cross-linking or uneven distribution of components; if the viscosity is too high, it may indicate localized over-gelatinization in the system or incomplete dispersion of particles.

[0106] Specifically, in the final stage of gelatinization, agarose gradually dissolves and participates in the initial formation of the network structure. This physical gelation reaction lays the foundation for the molecular arrangement of the wide powder in the subsequent cooling stage. In addition, the hydrogen bonding effect of polyols during the gelatinization process further strengthens the binding force of the starch molecular chain, making the viscoelastic performance of the slurry more stable.

[0107] In this embodiment, the gelatinized slurry is placed in a constant temperature insulation tank, and the insulation temperature is controlled at 70°C. The purpose of constant temperature insulation is to maintain the fluidity of the slurry and avoid the increase of viscosity due to cooling, which affects the extrusion effect. In general, the dynamic viscosity of the gelatinized slurry should be maintained between 20,000 and 30,000 mPa·s (measurement conditions: 70°C, shear rate 50s -1 ) to ensure good extrudability.

[0108] As an option, the slurry is extruded by a screw extruder, and the speed of the screw is controlled at 40-60rpm. A custom mold is provided at the outlet of the extruder, and the opening size of the mold is determined according to the specifications of the wide powder. In this embodiment, the mold opening width is 6mm and the mold thickness is 1.8mm, which can meet the market demand for wide powder.

[0109] Specifically, during the extrusion process, the temperature at the die outlet needs to be maintained at 65-70°C to prevent local condensation of the slurry during the extrusion process. The mold material is preferably food-grade stainless steel, which has good thermal conductivity and can maintain a uniform temperature when the slurry flows through the mold.

[0110] In one possible implementation, to further optimize the fluidity of the slurry, the screw and the inner wall of the die of the extruder are coated with a food-grade anti-stick coating. This coating can significantly reduce the adhesion of the slurry under high temperature and high pressure conditions, improve extrusion efficiency, and ensure the smoothness and consistency of the wide powder surface.

[0111] The wide powder after extrusion flows out of the die in a continuous strip shape and is then cut into the desired length by a cutting device. In this embodiment, the cutting length of the wide powder is controlled within 20 cm to facilitate subsequent cooling and drying. In some embodiments, to prevent the wide powder from deforming or sticking during cutting, a small amount of coolant (e.g., 5% deionized water) can be sprayed on the cutting tool.

[0112] The extrusion pressure in this embodiment is closely related to the slurry flow rate, and the relationship can be expressed by the following formula:

[0113] in:

[0114] Indicates the extrusion pressure, in Pa;

[0115] Indicates the dynamic viscosity of the slurry, in mPa·s;

[0116] Indicates the flow rate of the slurry in the mold, in m / s;

[0117] Indicates the outlet diameter of the mold, in meters.

[0118] In actual operation, the extrusion pressure needs to be kept constant to ensure that the thickness and width of the wide powder are uniform. Pressure fluctuations may cause the wide powder to break or have size deviations, so a pressure control system is used in this embodiment to monitor and adjust the extrusion process in real time.

[0119] In some embodiments, in order to improve the transparency of the wide powder, the temperature gradient at the die outlet can be increased during the extrusion process to further optimize the arrangement of the molecular chains of the slurry when it flows through the die. This optimization can reduce the tiny bubbles and structural defects inside the wide powder, thereby improving the visual quality of the product.

[0120] In this embodiment, the wide powder after molding directly enters the cooling water from the mold outlet, the cooling water temperature is controlled at 5-10, and the cooling time is 3-5 minutes. The low temperature of the cooling water can quickly reduce the overall temperature of the wide powder, inhibit the decomposition of the cross-linked network, and accelerate the gelation process of agarose. As an option, the temperature stability of the cooling water can be maintained by a circulating cooling system to avoid water temperature fluctuations caused by mass production.

[0121] Specifically, agarose changes from a solution state to a gel state during cooling, and its gelation temperature ranges from 30 to 40 degrees. During this process, agarose molecules form a three-dimensional network structure through hydrogen bonds and van der Waals forces. This network structure can not only fill the internal pores of the wide powder, but also fix the spatial arrangement of starch molecular chains and improve the transparency of the wide powder. The kinetic process of gelation can be described by the following formula:

[0122] in:

[0123] represents the rate constant;

[0124] represents the activation energy of gelation;

[0125] is the gas constant;

[0126] is the cooling water temperature (unit: K).

[0127] Generally, the lower the temperature of the cooling water, the higher the gelation rate, but too low a temperature may cause the surface layer to solidify too quickly, affecting the internal heat transfer efficiency. Therefore, this embodiment controls the water temperature within the above range to ensure cooling uniformity and the integrity of the internal structure.

[0128] As a possible implementation, in the present embodiment, 0.1% chitosan solution is added to cooling water to further improve the mechanical strength and structural stability of the wide powder surface. Chitosan interacts weakly with starch and konjac gum under the condition of pH value of 5.5-6.5, forming a uniform adsorption layer on the wide powder surface. This surface enhancement treatment can significantly improve the fracture resistance of the wide powder.

[0129] In some embodiments, cooling water spraying can be used instead of traditional immersion cooling. Spray cooling has the advantages of high cooling efficiency and water conservation, and is particularly suitable for continuous production lines. In spray cooling, the design of the nozzle angle and water flow rate needs to be adjusted according to the size and thickness of the wide powder to ensure that the water flow covers a wide range and the cooling is uniform.

[0130] In order to avoid deformation or adhesion of the wide noodles during the cooling process, this embodiment uses a stainless steel support frame to hold the wide noodles. The slot size on the support frame is slightly larger than the width and thickness of the wide noodles, which can provide a good support effect while not hindering the flow of cooling water. As an option, a food-grade anti-stick coating can also be applied to the surface of the support frame to further reduce the risk of adhesion between the wide noodles and the supporting material.

[0131] The temperature of the wide powder after cooling is generally controlled below 10, its internal structure is basically fixed, the surface is smooth and the transparency is good. After cooling, the wide powder needs to be quickly transferred to the next process to avoid secondary expansion or surface condensation caused by the increase in ambient temperature.

[0132] In the present embodiment, the wide powder after cooling is laid flatly on the conveyor belt of drying equipment.What drying equipment adopts is continuous hot air dryer, and drying temperature is controlled between 45-55, and drying time is 6-8 hours.Generally speaking, drying temperature can not be too high, in order to avoid destroying the gel structure of agarose and the molecular cross-linking strength of konjac glucomannan, chitosan.Low-temperature drying can keep the smooth surface and high transparency of wide powder, avoids producing micro-cracks simultaneously.

[0133] As an option, the flow rate of the hot air during the drying process is preferably 2-3 m / s, which can ensure that the hot air evenly covers the surface of the wide noodles and improve the water evaporation efficiency. Specifically, the humidity of the hot air needs to be controlled within the range of 30%-50% to avoid the phenomenon that the surface of the wide noodles dries too quickly and the internal moisture content is too high. In some embodiments, in order to further optimize the drying effect, the hot air can be divided into two layers, upper and lower, to flow alternately, so as to achieve a more uniform drying process.

[0134] In one possible implementation, when the wide flour is conveyed in the drying equipment, it should be placed in a single layer without overlapping. The conveyor belt is made of food-grade stainless steel mesh belt with a mesh size of 2-5mm to facilitate the penetration of hot air and the discharge of moisture. During the drying process, in order to prevent the wide flour from sticking to the contact part of the conveyor belt, a layer of food-grade anti-stick coating can be applied on the surface of the conveyor belt.

[0135] Specifically, the drying rate of wide powder can be expressed by the following formula:

[0136] in:

[0137] is the drying rate, in g / h;

[0138] is the initial moisture content of wide flour, in g;

[0139] is the moisture content of the wide flour when dried to time, in g;

[0140] is the drying time in h.

[0141] In some embodiments, in order to further improve the drying uniformity, the temperature can be lowered to 45°C in the later stage of the drying process so that the distribution of moisture inside the wide flour and the moisture on the surface tend to be consistent. The low temperature treatment at this stage can effectively prevent the wide flour from generating internal stress due to excessive moisture gradient.

[0142] In this embodiment, an online moisture monitoring device is used to monitor the moisture changes during the drying process in real time. Online detection can adjust the drying parameters in time to ensure that the moisture content of the wide noodles is stable within the range of 12%-14%. If the moisture content is too low, the wide noodles may become too brittle, affecting their mechanical strength; if the moisture content is too high, the quality may deteriorate during storage.

[0143] After drying, the wide noodles are transferred to a cooling room to gradually cool to room temperature (25). After cooling, the wide noodles should be packaged immediately to avoid re-contact with moisture in the air and moisture absorption. In some embodiments, vacuum packaging technology can be used to further extend the shelf life of the wide noodles and prevent quality changes caused by oxidation during the packaging process.

[0144] Embodiment 1:

[0145] Ingredients

[0146] Weigh 60% sweet potato starch, 15% tapioca starch, 8% corn starch, 3.5% konjac gum, 1.5% xanthan gum, 0.2% chitosan, 1% agarose, 1.5% glycerol, and 0.4% sodium citrate, and mix thoroughly to form a dry mixture.

[0147] Mixing

[0148] The dry mixture was added to water and the water ratio was adjusted to a slurry water content of 28%. The stirring speed was controlled at 1000 rpm for 8 minutes until the slurry was uniform and free of particles.

[0149] Gelatinization

[0150] Heat the slurry to 72°C, slowly raise the temperature to 88°C, and maintain for 12 minutes. At this point, the starch granules are completely gelatinized, and the konjac gum and xanthan gum form a preliminary physical cross-linking network. The process requires dynamic stirring at a shear rate of 50 rpm to prevent slurry stratification and ensure sufficient cross-linking.

[0151] forming

[0152] After gelatinization, the slurry is extruded into a wide powder shape with a thickness of about 1.8mm and a width of 6mm through an extruder. The wide powder after forming needs to be handled immediately to avoid excessive cooling that leads to uneven cross-linking.

[0153] cool down

[0154] Place the wide flour in 5% cooling water and soak for 4 minutes. Add a small amount of chitosan solution (concentration 0.1%) to the cooling water to enhance the electrostatic adsorption of the molecular chain during the cooling process and improve the strength of the finished product.

[0155] dry

[0156] The cooled wide powder enters the drying oven, the temperature is controlled at 50, and the drying time is 8 hours, until the moisture content of the wide powder reaches 13%.

[0157] Embodiment 2:

[0158] Ingredients

[0159] Take 58% sweet potato starch, 12% cassava starch, 7% corn starch, 4% konjac gum, 1% xanthan gum, 1.2% agarose, 1.2% glycerol, 0.3% sodium citrate, and 0.2% chitosan, and mix the above materials evenly to form a dry powder.

[0160] Mixing

[0161] According to the mass ratio of dry powder to water of 1:2.5, add the mixed powder into water and stir evenly. The speed of the high-speed mixer is 1200rpm, stir for 10 minutes to ensure that the slurry is uniform and free of bubbles.

[0162] Gelatinization

[0163] The slurry is slowly heated to 70°C, and then continuously heated to 90°C for 10 minutes. This process activates the gelatinization of starch granules, and agarose begins to dissolve, forming a synergistic cross-linking network with konjac gum and xanthan gum.

[0164] forming

[0165] After the slurry is cooled to 70°C, it is extruded through a die to form a wide powder with a thickness of 1.5 mm and a width of 5 mm. The operation must be quick to prevent the slurry from sticking to the die and affecting the molding effect.

[0166] cool down

[0167] Place the formed wide powder in 8% cooling water and cool for 3 minutes to allow the agarose to completely gel. The cooling water needs to be replaced regularly to avoid the cooling effect being weakened due to the increase in water temperature.

[0168] dry

[0169] The cooled wide powder is transferred to the drying equipment, the drying temperature is 45, and the drying time is continued for 9 hours until the moisture content is 12%.

[0170] Embodiment 3:

[0171] Ingredients

[0172] Weigh 62% sweet potato starch, 13% tapioca starch, 5% corn starch, 3% konjac gum, 1.5% xanthan gum, 1.2% agarose, 1.8% glycerol, 0.3% chitosan, and 0.4% sodium citrate. Mix well and set aside.

[0173] Mixing

[0174] The dry powder was mixed with water in a mass ratio of 1:2 and stirred for 8 minutes at a speed of 800 rpm until a uniform slurry was formed.

[0175] Gelatinization

[0176] Heat the slurry to 68, gradually increase the temperature to 85, and keep warm for 15 minutes. During the gelatinization process, the dynamic stirring rate is controlled at 60rpm to prevent the slurry from sticking to the pan. At this time, the polyols cross-link with the starch molecular chains to enhance the viscoelasticity.

[0177] forming

[0178] The gelatinized slurry is extruded through a die, and the thickness of the wide powder is controlled at 2mm and the width is 6mm. The gelatinized state of the slurry is uniform and the molding effect is good.

[0179] cool down

[0180] The formed wide powder is immersed in cooling water (5) and rapidly cooled for 2 minutes to prevent excessive crystallization of the molecular chain which may cause the wide powder to become brittle.

[0181] dry

[0182] The cooled wide powder was dried at 55°C for 6 hours, and the final moisture content was 12%.

[0183] Embodiment 4:

[0184] Ingredients

[0185] Take 65% sweet potato starch, 15% tapioca starch, 6% corn starch, 2.5% konjac gum, 1% xanthan gum, 0.1% chitosan, 0.8% agarose, 1.5% glycerol, and 0.3% sodium citrate. Mix well and set aside.

[0186] Mixing

[0187] Add the dry powder to water at a ratio of 1:2, stir at 1000 rpm for 5 minutes until the slurry is completely mixed.

[0188] Gelatinization

[0189] Heat the slurry to 65°C, gradually increase the temperature to 88°C, and keep warm for 10 minutes. At this time, the starch molecular chains are fully unfolded, and the xanthan gum and konjac gum work together to form a preliminary cross-linked structure.

[0190] forming

[0191] The slurry is extruded through a die to form a film with a thickness of 2.5 mm and a width of 8 mm. After forming, it needs to be directly processed into the next step.

[0192] cool down

[0193] The wide powder was immersed in 7°C cooling water and cooled for 4 minutes. Chitosan (0.1% concentration) was added during the cooling process to enhance the surface strength of the wide powder.

[0194] dry

[0195] The cooled wide powder was dried at 50°C for 9 hours and the moisture content was controlled at 13%.

[0196] Embodiment 5:

[0197] Ingredients

[0198] Weigh 60% sweet potato starch, 15% tapioca starch, 7% corn starch, 3.5% konjac gum, 1% xanthan gum, 1% agarose, 1% glycerol, 0.3% sodium citrate, and 0.2% chitosan. Mix well and set aside.

[0199] Mixing

[0200] The mixed powder and water were stirred in a ratio of 1:2.2, with a high-speed homogenizer at 1200 rpm for 6 minutes until a uniform slurry was obtained.

[0201] Gelatinization

[0202] The slurry was heated to 70°C, then raised to 85°C and kept warm for 15 minutes. During this period, the dynamic shear rate was controlled at 50 rpm to avoid uneven gelatinization.

[0203] forming

[0204] After gelatinization, it is extruded through a die to form a wide powder with a thickness of 2 mm and a width of 6 mm.

[0205] cool down

[0206] Immerse the molded wide powder in 5 cooling water, cool for 3 minutes, and solidify quickly.

[0207] dry

[0208] The cooled wide powder was placed in a 45 degree drying oven and dried for 7 hours until the moisture content reached 12%.

[0209] Comparative Example 1:

[0210] Ingredients

[0211] Take 60% sweet potato starch, 15% cassava starch, 8% corn starch, 3.5% konjac gum, and 1.5% xanthan gum. Do not add chitosan and agarose. Other components and proportions remain unchanged, including 1.5% glycerol and 0.4% sodium citrate. Mix and set aside.

[0212] Mixing

[0213] Add the dry powder into water at a dry powder to water mass ratio of 1:2.6, and stir until the slurry is uniform. The stirring time is 6 minutes and the rotation speed is 800 rpm.

[0214] Gelatinization

[0215] The slurry was heated to 68°C and continued to rise to 88°C for 8 minutes. The dynamic shear rate during gelatinization was 40 rpm.

[0216] forming

[0217] The gelatinized slurry was extruded through a die into a wide powder shape with a thickness of 1.8 mm and a width of 6 mm.

[0218] cool down

[0219] The formed wide powder was immersed in 7°C cooling water and cooled for 4 minutes without adding chitosan solution.

[0220] dry

[0221] The cooled wide powder was transferred to a drying oven and dried at 50°C for 8 hours with the moisture content controlled at 13%.

[0222] Comparative Example 2:

[0223] Ingredients

[0224] Take 60% sweet potato starch, 20% tapioca starch, 5% corn starch, 2.5% konjac gum, and 2% xanthan gum. Do not use polyols (glycerol or sorbitol). The remaining components remain the same, including 1.2% agarose, 0.3% sodium citrate, and 0.2% chitosan.

[0225] Mixing

[0226] The dry powder and water were mixed at a mass ratio of 1:2.4, with a mixer speed of 1000 rpm and a stirring time of 10 minutes until the slurry was fully uniform.

[0227] Gelatinization

[0228] The slurry was heated to 65°C, then raised to 85°C and kept at this temperature for 10 minutes. No dynamic shear was added during the process, and static heating was maintained.

[0229] forming

[0230] The gelatinized slurry is extruded through a die to form a wide powder with a thickness of 2 mm and a width of 5 mm.

[0231] cool down

[0232] Immerse the formed wide noodles in cooling water with a temperature of 10 and a cooling time of 3 minutes.

[0233] dry

[0234] The cooled wide powder was dried at 45°C for 9 hours, and the final moisture content of the wide powder was controlled at 12%.

[0235] Comparative Example 3:

[0236] Ingredients

[0237] Sweet potato starch 60%, cassava starch 15%, corn starch 10%, konjac gum 2%, xanthan gum 2%. Agarose was not used, and the other components remained the same, including glycerol 1.5%, chitosan 0.3%, and sodium citrate 0.3%.

[0238] Mixing

[0239] Add the dry powder into water at a ratio of 1:2.5, stir for 7 minutes at a speed of 900 rpm, and make the slurry fully uniform for later use.

[0240] Gelatinization

[0241] The slurry was heated to 68°C, then raised to 86°C, and kept at this temperature for 12 minutes. Dynamic shearing was performed during the gelatinization process, and the shear rate was 50 rpm.

[0242] forming

[0243] The gelatinized slurry is extruded through a die into wide powder with a thickness of 1.8 mm and a width of 6 mm.

[0244] cool down

[0245] The molded wide powder was immersed in 5% cooling water for 2 minutes. No chitosan solution was added during the cooling process.

[0246] dry

[0247] The cooled wide powder enters the drying equipment and is dried at 55 for 7 hours, with the moisture content controlled at 12%.

[0248] Comparative Example 4:

[0249] Ingredients

[0250] Take 65% sweet potato starch, 15% cassava starch, 6% corn starch, 3% konjac gum, 1% xanthan gum, and 1.5% agarose. Do not use chitosan, and keep the other components unchanged, including 1.5% glycerol and 0.3% sodium citrate.

[0251] Mixing

[0252] Add the dry powder into water at a dry powder to water mass ratio of 1:2.3 and stir for 8 minutes at a stirring speed of 1000 rpm.

[0253] Gelatinization

[0254] The slurry was heated to 70°C, raised to 90°C, and kept at this temperature for 10 minutes. No dynamic stirring was performed during the gelatinization process.

[0255] forming

[0256] The gelatinized slurry is extruded through a die, and the thickness of the wide powder is controlled at 2 mm and the width is 8 mm.

[0257] cool down

[0258] Immerse the molded wide powder in 8 cooling water and cool for 4 minutes. No auxiliary ingredients are added to the cooling water.

[0259] dry

[0260] The cooled wide powder was transferred to the drying equipment and dried at 50°C for 8 hours, with the moisture content controlled at 13%.

[0261] Comparative Example 5:

[0262] Ingredients

[0263] Sweet potato starch 60%, tapioca starch 20%, corn starch 5%, konjac gum 4%, xanthan gum 1%, agarose 1%, glycerol 1.2%. No sodium citrate and chitosan added.

[0264] Mixing

[0265] The dry powder was added to water in a ratio of 1:2 and stirred for 6 minutes at a speed of 1000 rpm until the slurry was uniform.

[0266] Gelatinization

[0267] The slurry was heated to 65°C, raised to 85°C, and kept at this temperature for 15 minutes. No dynamic shear was performed during the gelatinization process.

[0268] forming

[0269] The gelatinized slurry is extruded through a die to form a wide powder with a thickness of 2 mm and a width of 6 mm.

[0270] cool down

[0271] The molded wide powder was immersed in 7°C cooling water and cooled for 3 minutes without adding chitosan or other reinforcing ingredients.

[0272] dry

[0273] The cooled wide powder was dried at 45°C for 7 hours, and the final moisture content was 12%.

[0274] Experiment 1: Wide flour toughness test

[0275] Experimental Description

[0276] Purpose

[0277] The effect of the technical solution in Example 1 on improving the toughness of wide flour was verified, especially the contribution of the multi-stage cross-linked network (synergistic effect of konjac gum, xanthan gum and chitosan) to the tensile strength and elongation at break of wide flour, and compared with Comparative Example 1.

[0278] Experimental materials and equipment

[0279] Wide noodle samples: Wide noodles prepared in Example 1 and Comparative Example 1

[0280] Tensile testing machine: accuracy ±0.1MPa

[0281] Cutting mold: cutting size 10cm×2cm

[0282] Humidity control box: used for sample storage (humidity 50%, temperature 25)

[0283] Experimental procedures

[0284] Sample preparation

[0285] The wide noodles prepared in Example 1 and Comparative Example 1 were cut into standard test strips with a size of 10 cm×2 cm and a thickness of 1.8 mm. Five replicate samples were prepared for each group of samples and stored in a humidity control box to ensure that the moisture content of the wide noodles was consistent before testing.

[0286] Equipment debugging

[0287] The tensile testing machine was set to a constant tensile speed of 50 mm / min and an initial clamping distance of 8 cm. The test environment was controlled at room temperature of 25.

[0288] Testing Process

[0289] Fix the sample on the fixture of the tensile testing machine, start the equipment to gradually stretch the sample until it breaks, and record the maximum tensile force (MPa) at break and the maximum extension length (cm) before break.

[0290] Data Recording

[0291] Measure the tensile strength and elongation at break of each sample. The tensile strength is calculated as follows:

[0292] Tensile strength (MPa) = maximum tensile force (N) / cross-sectional area (cm ² )

[0293] The elongation at break is calculated as follows:

[0294] Elongation at break (%) = (elongation at break / initial clamping distance) × 100

[0295] Table 1

[0296] The tensile strength and elongation at break of the wide powder in Example 1 are much higher than those in the comparative example. This is not accidental. Chitosan plays a key role in the multi-level cross-linked network. Its electrostatic adsorption obviously makes the starch and other components more tightly combined. There is also agarose, which forms a gel structure after cooling, which effectively fills the tiny gaps between molecules. These microscopic improvements make the macroscopic performance stronger. The comparative example lacks these two components, so the tensile performance is naturally worse.

[0297] The introduction of dynamic shearing rearranges the molecular chains during the gelatinization stage. This link was ignored in the comparative example, resulting in uneven molecular distribution. The toughness was insufficient, and the sample broke quickly after being stretched to a certain length during the test. The wide powder of the embodiment can withstand greater tensile force, and this gap reflects the advantage of the technical solution at the molecular level.

[0298] The distribution of test data is interesting. The toughness of the example samples is not only strong, but also stable. The numerical fluctuations of tensile strength and elongation are very small, indicating that the technical solution has high repeatability. In the comparative example, the data is not only low, but also distributed in a messy manner. This may indicate that the lack of cross-linking components makes the preparation process more sensitive to environmental parameters, resulting in inconsistent product performance. The results are predictable, and the process optimization is directly reflected in the performance indicators.

[0299] Experiment 2: Transparency test of wide powder

[0300] Experimental Description

[0301] Purpose

[0302] The optical transparency of the wide powder prepared in different embodiments and comparative examples was tested to evaluate the effect of the invention on improving the appearance of the wide powder.

[0303] Experimental Materials

[0304] Wide noodle samples prepared in Example 1, Example 2, Example 3, Comparative Example 2 and Comparative Example 3.

[0305] Experimental equipment

[0306] UV-Vis spectrophotometer (wavelength range 400nm-800nm, test wavelength 600nm), transparent plastic sample holder.

[0307] Experimental procedures

[0308] Sample preparation

[0309] Cut wide powder slices of 2 cm × 2 cm and 1.5 mm thick from the wide powder prepared in each group. Make sure the sample surface is flat and free of wrinkles, bubbles or contamination.

[0310] The wide powder samples were placed at a relative humidity of 25% and 50% for 12 hours to ensure the moisture balance of the samples and avoid affecting the transmittance due to excessive dryness or humidity.

[0311] Equipment calibration

[0312] Turn on the spectrophotometer, warm it up for 15 minutes, and perform background calibration using air and a transparent plastic clip to ensure that the baseline transmittance is 100%.

[0313] Sample testing

[0314] Clamp the samples one by one into the center of the optical path of the spectrophotometer, ensuring that the light passes perpendicularly through the sample surface.

[0315] Set the wavelength to 600 nm and record the transmittance (%) of each sample.

[0316] Each sample was tested 3 times and the average value was taken.

[0317] Data Recording

[0318] The three transmittance test results of each group of samples were recorded in the experimental table and summarized as the final data.

[0319] Table 2

[0320] The wide powder of Example 1 has the best light transmittance performance, reaching 93.5%. From the perspective of molecular structure, this is inseparable from the synergistic effect of agarose, chitosan and polyols. Agarose quickly forms a dense gel network during the cooling process, and chitosan further stabilizes the arrangement of the molecular chains. The final result is that the internal structure of the wide powder is more uniform, and there is almost no scattering when light passes through. Comparative Example 1 is much worse, with a light transmittance of only 81.5%. Without chitosan, the connection between the molecular chains is not stable enough, the structure is loose, and the light scattering is naturally more, and the transparency is incomparable.

[0321] The problem of comparative example 3 is more prominent, with a light transmittance of only 75.5%. Without agarose, the wide powder does not form an effective gel network at all when it is cooled, and the molecular chains seem to be randomly stacked together. As soon as the light passes through, it is dispersed by the messy molecular arrangement. In contrast, in Example 1, the molecular chains are arranged neatly and compactly, with almost no gaps inside, and the maximum transparency effect can be maintained when light passes through. This gap is very intuitive, and it also illustrates the key role of agarose in improving the transparency of wide powder.

[0322] The light transmittance of Example 2 reached 90.4%, but the key was that the amount of polyol was insufficient, and the cross-linking strength of the molecular chain was slightly poor, resulting in an insufficiently dense local structure. In contrast, the design of Example 1 is more comprehensive, and several components work together to form an ideal molecular network structure, which not only makes the wide powder more transparent, but also significantly improves the overall texture. The data speaks for itself, and the solution of Example 1 does solve the problem of insufficient transparency of alum-free wide powder.

[0323] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A kind of alum-free wide flour, characterized in that, include: It is composed of the following components in percentage by weight: 55%-65% sweet potato starch; Cassava starch 10%-20%; Corn starch 5%-10%; Konjac gum 2%-5%; Xanthan gum 0.5%-2%; Chitosan 0.1%-0.3%; Agarose 0.5%-1.5%; 0.5%-2% polyol, wherein the polyol is glycerol or sorbitol; Weak acid stabilizer 0.3%-0.5%, wherein the weak acid stabilizer is sodium citrate or sodium lactate; Moisture content 20%-30%.

2. A kind of alum-free wide flour according to claim 1, characterized in that, The sweet potato starch is a refined sweet potato starch with a moisture content of 10%-14% and a viscosity of 5000-7000 mPa·s, and the cassava starch is an industrial-grade cassava starch with a gelatinization temperature of 62-70°C.

3. A kind of alum-free wide flour according to claim 1, characterized in that, The corn starch has an amylose content of 25%-28% and a particle size distribution range of 5-20 microns.

4. A kind of alum-free wide flour according to claim 1, characterized in that, The viscosity of the konjac gum is 20000-30000 mPa·s in a 0.5% aqueous solution under the condition of 25, and the particle size is 80-120 meshes.

5. A kind of alum-free wide flour according to claim 1, characterized in that, The xanthan gum is food grade xanthan gum with a purity of more than 95%, and its solubility is preferably more than 85 and completely dissolved.

6. A kind of alum-free wide flour according to claim 1, characterized in that, The chitosan has a molecular weight of 100,000-200,000 Daltons, a deacetylation degree of 70%-90%, and a dispersion property that forms a uniform and stable solution under a pH of 4-6.

7. A kind of alum-free wide flour according to claim 1, characterized in that, The molecular weight of the agarose is 150,000-200,000 Daltons, the dissolution temperature is 85-90°C, and the gelation temperature is 30-40°C.

8. A kind of alum-free wide flour according to claim 1, characterized in that, The polyol is glycerol, the content of which is 1%-2%, and is used to construct a cross-linked network that forms hydrogen bonds with starch molecular chains.

9. A kind of alum-free wide flour according to claim 1, characterized in that, The weak acid stabilizer is sodium citrate, and its addition amount is controlled at 0.3%-0.4%. Its function is to maintain the pH value of the slurry at 5.5-6.5 to stabilize the molecular cross-linking.

10. A method for preparing alum-free wide flour, according to the alum-free wide flour according to any one of claims 1 to 9, characterized in that: The following steps are involved: Step 1, mixing sweet potato starch, tapioca starch and corn starch, adding konjac gum, xanthan gum, chitosan, agarose, polyol and weak acid stabilizer to form a dry mixture; Step 2: Add the dry mixture into water and stir evenly to form a slurry; Step 3: Heat the slurry to 65-90°C, maintain for 8-15 minutes, and perform dynamic shearing to form a preliminary cross-linked network; Step 4: Extruding the gelatinized slurry into a wide powder shape through a die; Step 5: Immerse the formed wide noodles in cooling water at a temperature of 5-10°C. Step 6: Place the cooled wide flour in a drying device and dry at 45-55 degrees to a moisture content of 12%-14%.